Analyzing Interpersonal Metafunction Through Mood and Modality in Kraine Agary's Yellow-Yellow from Critical Discourse and Womanist Perspective - Koussouhon, Léonard (My University, 2015)
Abstract
Keywords: Mood; modality; deontic; epistemic; commitment; ideologies